Determination of Triterpenoids in Perilla frutescens by High Performance Liquid Chromatography Based on Matrix Solid Phase Dispersion - MA, YINHAI; PENG, YONGFANG; FAN, PENG; YANG, GUANGYU; HU, QIUFEN (Asian Journal of Chemistry, 2010)
A new high performance liquid chromatography method based on matrix solid phase dispersion for the simultaneous determination of the major triterpenoids in Perilla frutescens (Chinese medicinal herb) was developed. The plant samples and silica gel (1:4) were homogenized in a mortar and then packed into a cartridge. The triterpenoids fraction was eluted from the cartridge with dichloromethane -acetone (85:15). The solvent were volatilized and the residue was dissolved with methanol. The triterpenoids was separated on a ZORBAX Stable Bound (4.6 mm × 100 mm, 1.8 μm) C18 column by gradient elution with acetonitrile and water as the mobile phase and detected with evaporative light scattering detection. This method provides good reproducibility and sensitivity for the quantification of bioactive triterpene acids i.e., tormentic acid, oleanolic acid and ursolic acid, respectively. The relative standard derivation of overall intra-day variations were less than 1.8 %, and inter-day variations were less than 2.3 %. The standard recoveries (at 3 different concentrations of markers: 0.1, 0.5 and 2.0 mg) were ranged from 97- 102 %.